Acute effects of aerobic exercise intensity on arterial stiffness after glucose ingestion in young men. (18th October 2016) - Kobayashi, Ryota; Hashimoto, Yuto; Hatakeyama, Hiroyuki; Okamoto, Takanobu
Summary: Arterial stiffness increases after glucose ingestion. Acute low‐ and moderate‐intensity aerobic exercise decreases arterial stiffness. However, the acute effects of 30 min of cycling at low‐ and moderate‐intensity [25% (LE trial) and 65% (ME trial) peak oxygen uptake, respectively] on arterial stiffness at 30, 60 and 120 min of a postexercise glucose ingestion. Ten healthy young men (age, 22·4 ± 0·5 years) performed LE and ME trials on separate days in a randomized controlled crossover fashion. Carotid–femoral (aortic) pulse wave velocity (PWV), femoral–ankle (leg) PWV, carotid augmentation index (AIx) and carotid blood pressure (BP) (applanation tonometry), brachial and ankle BP (oscillometric device), heart rate (HR) (electrocardiography), blood glucose (UV‐hexokinase method) and blood insulin (CLEIA method) levels were measured at before (baseline) and at 30, 60 and 120 min after the 75‐g OGTT. Leg PWV, ankle pulse pressure and BG levels significantly increased from baseline after the 75‐g OGTT in the LE trial ( P <0·05), but not in the ME trial. Insulin levels and HR significantly increased from baseline after the 75‐g OGTT in both trials ( P <0·05). Aortic PWV, carotid AIx, brachial BP and carotid BP did not change from baseline after the 75‐g OGTT in both trials. The present findings indicate that aerobic exercise at moderate intensity before glucose ingestion suppresses increases leg arterial stiffness after glucose ingestion.